Methodology for static tuning of the HEV fuel flow measuring system - Bozhkov, S T; Milenov, I; Petrov, R V; Leontiev, V S; Bozhkov, P (IOP conference series. Materials Science and Engineering, 2020)
The modern automobiles are subject of more stringent requirements [1] corresponding to power, torque, fuel economy and ecology legislations, which is led to designing of new power sources and constructions, such as the hybrid electric vehicles (HEV). They are moving by the energy [2], which is ensured by the internal combustion engine (ICE) and the battery. The main factor in this area is the HEV fuel system, which is controlled by the electronic control unit (ECU) [1]. The electronic control of the Spark Ignition Engines (SI engines), as well as the Direct Ignition Engines (DI engines) is based on the certain sensors signals, program maps and management algorithms. The result in this electronic control is the management of the fuel injectors. The management of the fuel injectors consists in the start of injection, injection duration, number of injection events, injection advance, injection pressure etc. Moreover, the fuel consumption and fuel efficiency are the main factors, which are determining the HEV advances. The learning and measuring the HEV fuel consumption, as well as, the conventional automobiles, is the ground for achievement of quality results in the education of the automotive engineers, as well as for obtaining of scientific researching for developments and innovations. Significant meaning in this concept has the real, live and practical performance with the help of testing equipment and test-benches. This paper renders the methodology of static tuning the Fuel Flow Measuring System EFMS100 on the test bench SAV-1 with the support of controller Matrix MIAC MI0245 and Flowcode 7 softwar.